Language Reforms and Development of the Azerbaijani Language - Yusifova Nazile (Theoretical Hypotheses and Empirical Results, 2024)
The Azerbaijani language, part of the Turkic language family, has undergone significant changes and reforms, particularly in the 20th century. Its evolution has been influenced by political, social, and cultural factors, which have shaped its current form.